Biomechanics of the mandible of Macaca mulatta during the power stroke of mastication: Loading, deformation, and strain regimes and the impact of food type. Issue 147 (October 2020) - Panagiotopoulou, Olga; Iriarte-Diaz, Jose; Mehari Abraha, Hyab; Taylor, Andrea B.; Wilshin, Simon; Dechow, Paul C.; Ross, Callum F.
Abstract: Mandible morphology has yet to yield definitive information on primate diet, probably because of poor understanding of mandibular loading and strain regimes, and overreliance on simple beam models of mandibular mechanics. We used a finite element model of a macaque mandible to test hypotheses about mandibular loading and strain regimes and relate variation in muscle activity during chewing on different foods to variation in strain regimes. The balancing-side corpus is loaded primarily by sagittal shear forces and sagittal bending moments. On the working side, sagittal bending moments, anteroposterior twisting moments, and lateral transverse bending moments all reach similar maxima below the bite point; sagittal shear is the dominant loading regime behind the bite point; and the corpus is twisted such that the mandibular base is inverted. In the symphyseal region, the predominant loading regimes are lateral transverse bending and negative twisting about a mediolateral axis. Compared with grape and dried fruit chewing, nut chewing is associated with larger sagittal and transverse bending moments acting on balancing- and working-side mandibles, larger sagittal shear on the working side, and larger twisting moments about vertical and transverse axes in the symphyseal region. Nut chewing is also associated with higher minimum principal strain magnitudes in the balancing-side posterior ramus; higher sagittal shear strain magnitudes in the working-side buccal alveolar process and the balancing-side oblique line, recessus mandibulae, and endocondylar ridge; and higher transverse shear strains in the symphyseal region, the balancing-side medial prominence, and the balancing-side endocondylar ridge. The largest food-related differences in maximum principal and transverse shear strain magnitudes are in the transverse tori and in the balancing-side medial prominence, extramolar sulcus, oblique line, and endocondylar ridge. Food effects on the strain regime are most salient in areas not traditionally investigated, suggesting that studies seeking dietary effects on mandible morphology might be looking in the wrong places.